POTENTIAL OF BLACK SOLDIER FLY (BSF) IN REDUCING MUNICIPAL FOOD LOSS AND WASTE (FLW) AT TAMAN SARI DISTRICT, WEST JAKARTA - Tasya Oemar; Pramiati Purwaningrum; Ratnaningsih Ruhiyat; Fitrio Ashardiono (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
Black Soldier Fly (BSF) larvae are known to have the ability to process food loss and waste and reduce the weight of food loss and waste, by producing decomposition products that have beneficial values. Food loss and waste needs to be reduced to reduce the burden of waste entering the Final Disposal (TPA). Aim: The purpose of this study was to determine the ability of BSF larvae and to determine the quality of the decomposition results in processing food loss and waste in the Taman Sari District on a laboratory scale. Methodology and Results: Taman Sari Distrisct is a high dense populated area Total days of bioconversion activity is 12 days, giving back 1,000 grams of municipal waste organic, containing food loss and food waste, according to variation is given repeatedly on the 1st, 5th, and 8th days for each 12 sample code. The amount of 5 days old (5-DOL) maggot used for each sample code is 30 grams. Conclusion, significance, and impact study: The percentage reduction in processing from 3 kg of food loss and waste can reach 86% with the average residue produced in the form of 415.67 grams of solid compost and 221.7 grams of prepupa. Bred prepupa will evolve into several stages: pupa, fly, egg, baby larvae, and 5-DOL for 57 days on its life cycle.